Fabrics, fabric bodies, and sheets

JP7943742B2Active Publication Date: 2026-10-30TORAY INDUSTRIES INC +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022011338
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-27
Publication Date
2026-10-30
Estimated Expiration
2042-01-27

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、優れた座り心地や通気を示し、かつ、優れた難燃性を示す布帛、布帛体およびシートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943742000004
    Figure 0007943742000004
  • Figure 0007943742000005
    Figure 0007943742000005
  • Figure 0007943742000001
    Figure 0007943742000001
Patent Text Reader

Abstract

To provide a fabric, a fabric body, and a sheet, which are excellent in appearance and comfortable to sit and have good air permeability and excellent fire retardancy.SOLUTION: A core-sheath conjugate fiber contains at least 50 mass% of monofilament, and the monofilament has a core part and a sheath part. 60 to 90% by volume of the core part is contained in the core-sheath conjugate fiber and the core part contains a first fire retardant and polyester elastomer. 10 to 40% by volume of the sheath part is contained in the core-sheath conjugate fiber and the sheath part is formed of polyester excluding the polyester elastomer of the core part.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to fabrics, fabric bodies, and sheets. More specifically, this invention relates to fabrics, fabric bodies, and sheets having good seating comfort, flame retardancy, and breathability. [Background technology]

[0002] Conventionally, fabrics for attaching to a frame and seating seats with fabrics attached to the frame have been developed (Patent Document 1). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2019-143283 [Overview of the project] [Problems that the invention aims to solve]

[0004] The fabric used for seat cushions needs to be flame-retardant to prevent the spread of fire in the event of a fire, for example. However, the fabric and seat cushion described in Patent Document 1 do not disclose how to impart flame retardancy. It is conceivable to impart flame retardancy to the fabric by adding a flame retardant. However, the flame retardant may appear on the surface as scum during the spinning and knitting processes. As a result, there are problems such as variations in the amount of flame retardant contained in the fabric, poor appearance, and inability to impart the desired flame retardancy.

[0005] This invention has been made in view of the above-mentioned conventional problems, and aims to provide a fabric, fabric body, and sheet that exhibit excellent appearance, seating comfort, breathability, and excellent flame retardancy. [Means for solving the problem]

[0006] The present invention, which solves the above problems, mainly includes the following configuration.

[0007] (1) A fabric comprising 50% by mass or more of monofilaments, wherein the monofilaments are core-sheath composite fibers having a core and a sheath, the core being present in 60-90% by volume relative to the core-sheath composite fiber and comprising a first flame retardant and a polyester elastomer, and the sheath being present in 10-40% by volume relative to the core-sheath composite fiber and comprising polyester excluding the polyester elastomer of the core.

[0008] With this configuration, the first flame retardant contained in the core is less likely to appear as scum during the spinning and knitting processes. As a result, the fabric has a superior appearance and maintains excellent flame retardancy. In addition, the fabric exhibits excellent seating comfort and breathability.

[0009] (2) The fabric according to (1), wherein the fabric is a knitted fabric, the knitted fabric has a knitting density of 10 to 50 threads / 25.4 mm in at least one of the warp and weft directions, and the fineness of the monofilament is 300 to 3000 dtex.

[0010] With this configuration, the fabric exhibits superior comfort and breathability.

[0011] (3) The fabric according to (1) or (2), wherein the first flame retardant comprises at least one selected from the group consisting of organophosphate ester compounds, phosphinate metal salts, and triazine skeleton-containing compounds, and is present in an amount of 1 to 30% by mass relative to the core.

[0012] With this configuration, the fabric is less prone to scum formation during processes such as spinning and knitting, and exhibits greater stability and superior flame retardancy.

[0013] (4) The fabric according to any one of (1) to (3), wherein the sheath portion contains a second flame retardant, the second flame retardant contains at least one of an arylphosphinate compound or an alkylphosphinate compound, and is present in the sheath portion in an amount of 0.3 to 1.1% by mass in terms of phosphorus element.

[0014] According to such a configuration, the fabric is less prone to generating scum in processes such as the spinning step and knitting step, and exhibits more stable and excellent flame retardancy.

[0015] (5) A fabric body comprising the fabric according to any one of (1) to (4) and a frame member.

[0016] According to such a configuration, the fabric body has an excellent appearance and excellent flame retardancy is easily maintained. In addition, the fabric body exhibits excellent seating comfort and air permeability.

[0017] (6) The fabric body according to (5), wherein the fabric is formed without sewing and without adhesion.

[0018] According to such a configuration, the fabric, which is free of sewing and adhesion, can be applied to various uses where formation of a three-dimensional fabric surface is desirable.

[0019] (7) A seat using the fabric body according to (5) or (6).

[0020] According to such a configuration, the seat easily maintains excellent flame retardancy. In addition, the seat exhibits excellent seating comfort and air permeability. Effects of the Invention

[0021] According to the present invention, it is possible to provide a fabric, a fabric body, and a seat that exhibit excellent seating comfort and air permeability, as well as excellent flame retardancy. Brief Description of the Drawings

[0022] [Figure 1] Figure 1 is a schematic diagram for explaining a method of attaching a frame member to a fabric. [Figure 2] Figure 2 is a schematic diagram of a fabric body. Modes for Carrying Out the Invention

[0023] (Fabric and Fabric Body) A fabric according to one embodiment of the present invention contains 50% by mass or more of monofilament. The monofilament is a core-sheath composite fiber having a core and a sheath. The core is present in 60-90% by volume relative to the core-sheath composite fiber and contains a first flame retardant and a polyester elastomer. The sheath is present in 10-40% by volume relative to the core-sheath composite fiber and consists of polyester excluding the polyester elastomer of the core.

[0024] Furthermore, the fabric body of one embodiment of the present invention comprises the fabric described above and a frame member. Each of these will be described below.

[0025] (fabric) The fabric contains 50% or more by mass of monofilament. Monofilament is a core-sheath composite fiber having a core and a sheath.

[0026] (core) The core contains a first flame retardant and a polyester elastomer.

[0027] (Polyester elastomer) Polyester elastomers are not particularly limited. For example, polyester elastomers include thermoplastic polyester elastomers. Thermoplastic polyester elastomer resins may consist of, for example, a high-melting-point crystalline segment mainly composed of crystalline aromatic polyester and a low-melting-point polymer segment mainly composed of aliphatic polyether units and / or aliphatic polyester units.

[0028] (High melting point crystallinity segment) The high-melting-point crystalline segment is a polyester formed from an aromatic dicarboxylic acid or its ester-forming derivative (hereinafter also referred to as the "acid component") and a diol or its ester-forming derivative (hereinafter also referred to as the "diol component").

[0029] Aromatic dicarboxylic acids include, for example, terephthalic acid, isophthalic acid, phthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, anthracenedicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethanedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sulfoisophthalic acid, and sodium 3-sulfoisophthalate.

[0030] In this embodiment, aromatic dicarboxylic acids may be primarily used. Some of the aromatic dicarboxylic acids may be replaced with alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, and 4,4'-dicyclohexyldicarboxylic acid, or with aliphatic dicarboxylic acids such as adipic acid, succinic acid, oxalic acid, sebacic acid, dodecanedionic acid, and dimer acid. Ester-forming derivatives of dicarboxylic acids (e.g., lower alkyl esters, aryl esters, carbonate esters, and acid halides) may also be used.

[0031] Diols are, for example, diols with a molecular weight of 400 or less. Diols with a molecular weight of 400 or less include aliphatic diols such as 1,4-butanediol, ethylene glycol, trimethylene glycol, pentamethylene glycol, hexamethylene glycol, neopentyl glycol, and decamethylene glycol; alicyclic diols such as 1,1-cyclohexanedimethanol, 1,4-dicyclohexanedimethanol, and tricyclodecanedimethanol; and aromatic diols such as xylylene glycol, bis(p-hydroxy)diphenyl, bis(p-hydroxy)diphenylpropane, 2,2'-bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxyethoxy)phenyl]sulfone, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 4,4'-dihydroxy-p-terphenyl, and 4,4'-dihydroxy-p-quarterphenyl. These diols can also be used in the form of esterifying derivatives (e.g., acetylated derivatives, alkali metal salts, etc.).

[0032] (Low melting point polymer segment) The low-melting-point polymer segment is at least one of either an aliphatic polyether or an aliphatic polyester.

[0033] Aliphatic polyethers include poly(oxyethylene) glycol, poly(oxypropylene) glycol, poly(oxytrimethylene) glycol, poly(oxytetramethylene) glycol, poly(oxyhexamethylene) glycol, ethylene oxide adducts of poly(oxypropylene) glycol, and copolymers of ethylene oxide and tetrahydrofuran. Among these, the aliphatic polyether is preferably poly(oxytetramethylene) glycol and / or ethylene oxide adducts of poly(oxypropylene) glycol and / or copolymers of ethylene oxide and tetrahydrofuran.

[0034] Aliphatic polyesters include poly(ε-caprolactone), polyenanthractone, polycapryloractone, polybutylene adipate, and polyethylene adipate.

[0035] The low-melting-point polymer segment is preferably poly(oxytetramethylene) glycol, ethylene oxide adduct of poly(oxypropylene) glycol, copolymer glycol of ethylene oxide and tetrahydrofuran, poly(ε-caprolactone), polybutylene adipate, polyethylene adipate, etc., from the standpoint of the excellent elastic properties of the resulting polyester block copolymer. More preferably, it is poly(oxytetramethylene) glycol, ethylene oxide adduct of poly(oxypropylene) glycol, and copolymer glycol of ethylene oxide and tetrahydrofuran.

[0036] The number-average molecular weight of the low-melting-point polymer segment is preferably 300 to 6000, and more preferably 1000 to 3000, in the copolymerized state. Because the number-average molecular weight of the low-melting-point polymer segment is within the above range, the resulting fabric exhibits excellent resistance to deformation, resulting in improved durability and superior seating comfort.

[0037] Returning to the overall explanation of polyester elastomers, it is preferable to use two types of polyester block copolymers (polyester block copolymer (A1) and polyester block copolymer (A2)) for the polyester elastomer constituting the core, from the viewpoint of improving flame retardancy by improving the dispersibility of the flame retardant, and improving the stretchability and heat shrinkability of the filament.

[0038] The polyester block copolymer (A1) comprises, for example, a high-melting-point crystalline segment (H1) whose main constituent unit is crystalline aromatic polyester, and a low-melting-point polymer segment (L1) whose main constituent unit is aliphatic polyether units and / or aliphatic polyester.

[0039] The polyester block copolymer (A1) may consist of a high-melting-point crystalline segment (H1) selected from the above acid components and one or more selected from the above diol components. The high-melting-point crystalline segment (H1) is, for example, a polybutylene terephthalate unit derived from terephthalic acid or dimethyl terephthalate and 1,4-butanediol.

[0040] The low-melting-point polymer segment (L1) may be selected from the above-mentioned aliphatic polyethers and / or aliphatic polyesters.

[0041] In the polyester block copolymer (A1), the preferred blending ratio of the high-melting-point crystalline segment (H1) to the low-melting-point polymer segment (L1) is 50-95% by mass for the high-melting-point crystalline segment (H1) and 5-50% by mass for the low-melting-point polymer segment (L1). More preferably, the blending ratio is 65-95% by mass for the high-melting-point crystalline segment (H1) and 5-35% by mass for the low-melting-point polymer segment (L1). Even more preferably, the blending ratio is 80-95% by mass for the high-melting-point crystalline segment (H1) and 5-20% by mass for the low-melting-point polymer segment (L1). By having the blending ratio of the high-melting-point crystalline segment (H1) to the low-melting-point polymer segment (L1) within the above range, the resulting fabric exhibits an excellent balance between heat resistance, durability, and processability.

[0042] The melting point of the polyester block copolymer (A1) is preferably 200°C to 225°C, and more preferably 210°C to 225°C. Having the melting point of the polyester block copolymer (A1) within this range ensures sufficient rigidity and heat resistance, as well as excellent resistance to deformation, in the resulting polyester elastomer.

[0043] The polyester block copolymer (A2) comprises a high-melting-point crystalline segment (H2) whose main constituent unit is crystalline aromatic polyester, and a low-melting-point polymer segment (L2) whose main constituent unit is aliphatic polyether units and / or aliphatic polyester.

[0044] The polyester block copolymer (A2) may consist of a high-melting-point crystalline segment (H2) composed of two or more acid components selected from the above-mentioned acid components and one or more diol components selected from the above-mentioned diol components. For example, the high-melting-point crystalline segment (H2) may be a combination of terephthalic acid and isophthalic acid, a combination of terephthalic acid and dodecanedionic acid, or a combination of terephthalic acid and dimer acid.

[0045] By using a polyester block copolymer (A2) containing two or more acidic components, the resulting polyester elastomer can improve the dispersibility of the flame retardant and suppress the aggregation of the flame retardant. As a result, the flame retardancy of the polyester elastomer is easily improved. Furthermore, the polyester elastomer can improve the stretchability and heat shrinkability of the filament.

[0046] The high-melting-point crystalline segment (H2) preferably consists of polybutylene terephthalate units derived from terephthalic acid and / or dimethyl terephthalate, and polybutylene isophthalate units derived from isophthalic acid and / or dimethyl isophthalate and 1,4-butanediol.

[0047] The low-melting-point polymer segment (L2) may be selected from the above-mentioned aliphatic polyethers and / or aliphatic polyesters.

[0048] In the polyester block copolymer (A2), the preferred blending ratio of the high-melting-point crystalline segment (H2) to the low-melting-point polymer segment (L2) is 40-90% by mass for the high-melting-point crystalline segment (H2) and 10-60% by mass for the low-melting-point polymer segment (L2). More preferably, the preferred ratio is 45-85% by mass for the high-melting-point crystalline segment (H2) and 15-55% by mass for the low-melting-point polymer segment (L2). Even more preferably, the preferred ratio is 70-85% by mass for the high-melting-point crystalline segment (H2) and 15-30% by mass for the low-melting-point polymer segment (L2).

[0049] The melting point of the polyester block copolymer (A2) is preferably 120°C to 170°C, and more preferably 130°C to 165°C. Because the melting point of the polyester block copolymer (A2) is within this range, when used in combination with the polyester block copolymer (A1), it contributes to improved dispersibility of flame retardants and other substances. As a result, the resulting fabric maintains its heat shrinkability and exhibits excellent abrasion resistance, toughness, flame retardancy, and appearance.

[0050] In the polyester elastomer of this embodiment, the blending ratio (parts by mass) of polyester block copolymer (A1) and polyester block copolymer (A2) is preferably 50 to 99 parts by mass of polyester block copolymer (A1) and 1 to 50 parts by mass of polyester block copolymer (A2), more preferably 60 to 95 parts by mass of polyester block copolymer (A1) and 5 to 40 parts by mass of polyester block copolymer (A2), and even more preferably 70 to 95 parts by mass of polyester block copolymer (A1) and 5 to 30 parts by mass of polyester block copolymer (A2). By having the blending ratio (parts by mass) of polyester block copolymer (A1) and polyester block copolymer (A2) within the above range, the resulting polyester elastomer exhibits excellent resistance to deformation and improved dispersibility of the flame retardant, resulting in superior toughness and flame retardancy.

[0051] Polyester block copolymer (A1) and polyester block copolymer (A2) can be produced by known methods. For example, polyester block copolymer (A1) and polyester block copolymer (A2) can be produced by a method in which a lower alcohol diester of a dicarboxylic acid is transesterified with an excess amount of low molecular weight glycol and a low melting point polymer segment component in the presence of a catalyst, and the resulting reaction product is polycondensed, or by a method in which a dicarboxylic acid is esterified with an excess amount of glycol and a low melting point polymer segment component in the presence of a catalyst, and the resulting reaction product is polycondensed.

[0052] Furthermore, the polyester elastomer of this embodiment may optionally contain additives such as antioxidants (phosphonite compounds, phosphite compounds, hypophosphite compounds, hindered phenol compounds, thioether compounds, etc.), ultraviolet absorbers (benzotriazole-based, benzophenone-based, etc.), light stabilizers (HALS: hindered amine compounds, etc.), antistatic agents (polyether ester amide, etc.), lubricants (stearyl alcohol, metal stearate, stearamide, glyceride stearate, etc.), dyes (organic dyes such as nigrosine), pigments (carbon black, titanium dioxide, etc.), plasticizers (phthalate-based, adipic acid-based, trimellitic acid-based, etc.), mold release agents (paraffin wax, saturated fatty acid ester-based, unsaturated fatty acid ester-based, etc.), and anti-esterification agents, or other thermoplastic resins such as styrene resins, olefin resins, and polyvinyl chloride resins may be added.

[0053] In addition to the organophosphorus-containing compounds exemplified as flame retardants, other phosphorus-containing compounds include hydrates of metal hypophosphite salts. By using hydrates of metal hypophosphite salts, polyester elastomers are more easily susceptible to oxidative degradation and have their surface appearance and color tone improved.

[0054] (First flame retardant) The first flame retardant is a flame retardant contained in the core. Preferably, the first flame retardant contains at least one selected from the group consisting of organic phosphate ester compounds, phosphinate metal salts, and triazine skeleton-containing compounds. As a result, the resulting fabric is less prone to scum formation during spinning and knitting processes, and exhibits greater stability, superior appearance, and flame retardancy.

[0055] Examples of organophosphate ester compounds include resorcinol phosphates such as tetrakis(2,6-dimethylphenyl)1,3-phenylenebisphosphate and resorcinolbis(diphenyl phosphate), hydroquinone phosphates such as hydroquinonebis(diphenyl phosphate), biphenol phosphates such as biphenolbis(diphenyl phosphate), and bisphenol phosphates such as bisphenol-Abis(diphenyl phosphate).

[0056] Organic phosphate ester compounds exhibit lower melting points than general thermoplastic polyester elastomers and have good compatibility with polyester elastomers. Therefore, organic phosphate ester compounds have excellent dispersibility during melt mixing. Furthermore, organic phosphate ester compounds can improve the flame retardancy of polyester elastomers while suppressing the decrease in mechanical strength properties.

[0057] Furthermore, aryl spirodiphosphinates, which are condensed with polyhydric alcohols such as pentaerythritol, are also suitably used as organophosphate ester compounds.

[0058] Furthermore, among organic phosphate ester compounds, diphosphinate compounds having a spiro-type ring condensation structure exhibit a high melting point, easier dispersibility in polyester elastomers, and high heat resistance. Therefore, diphosphinate compounds having a spiro-type ring condensation structure are more preferably used because they can suppress bleed-out during processing.

[0059] The melting point of aryl spirodephosphinate is preferably between 100 and 300°C. Having a melting point within this range makes aryl spirodephosphinate less prone to bleed-out during melt processing, and also improves dispersibility and processability during melt processing. As a result, the toughness, fatigue resistance, and surface appearance of the resulting filaments and molded products tend to be improved.

[0060] The acid value of the aryl spirodephosphinate is preferably 1.0 mg KOH / g or less, and more preferably 0.5 mg KOH / g or less. When the acid value is within the above range, the resulting polyester elastomer exhibits excellent flame retardancy and color. Furthermore, filaments using the resulting polyester elastomer tend to exhibit less deterioration in heat aging resistance and hydrolysis resistance.

[0061] Arylspirodiphosphinates include, for example, pentaerythritol diphosphinate compounds. Specifically, pentaerythritol diphosphinate compounds include 2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane,3,9-dibenzyl-3,9-dioxide, 2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane,3,9-diα-methylbenzyl-3,9-dioxide, 2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane,3,9-di(2-phenylethyl)-3,9-dioxide, and 2,4,8,10-tetraoxa-3,9-diphosphaspiro[5,5]undecane,3,9-bis(diphenylmethyl)-3,9-dioxide.

[0062] The content of the organic phosphate ester compound is preferably 1% by mass or more, and more preferably 10% by mass or more, relative to the entire core. Furthermore, the content of the organic phosphate ester compound is preferably 30% by mass or less, and more preferably 20% by mass or less, relative to the entire core. By having the content of the organic phosphate ester compound within the above range, the resulting fabric does not impair heat shrinkability and has excellent toughness, flame retardancy, and appearance.

[0063] The metal phosphinate salt has the general formula R 1 R 2 P(=O)OM or [{OP(=O)R 1}-R 3 -{P(=O)R 2 This is a group of compounds described as -O}]M. 1 and R 2R is an organic group that may be the same or different. 3 M is methylene, ethylene, n-propylene, isopropylene, n-butylene, t-butylene, phenylene, or naphthylene, and may have various substituents on its aromatic ring. M is aluminum, zinc, calcium, or magnesium.

[0064] Specific examples of metal phosphinate salts (also called metal phosphinate compounds) include metal phosphinate salts with aliphatic hydrocarbon groups substituted, such as metal salts of diethyl phosphinate and metal salts of methyl ethyl phosphinate, and it is preferable that they be aluminum phosphinate salts (aluminum diethyl phosphinate) or zinc phosphinate salts (zinc diethyl phosphinate). Among these, aluminum phosphinate salts are more preferable because they greatly improve the flame retardancy of polyester elastomers and suppress bleed-out during processing.

[0065] The content of the phosphinate metal salt is preferably 1% by mass or more, and more preferably 10% by mass or more, relative to the entire core. Furthermore, the content of the phosphinate metal salt is preferably 30% by mass or less, and more preferably 20% by mass or less, relative to the entire core. By having the phosphinate metal salt content within the above range, the resulting polyester elastomer has excellent flame retardancy and excellent processability.

[0066] Furthermore, by pre-melting the organophosphorus-containing compound and the phosphinate metal salt together with the above-mentioned polyester elastomer within a specific range to prepare a flame-retardant masterbatch, and then further melt-melting the flame-retardant masterbatch with the polyester elastomer, the aggregation of the organophosphorus-containing compound can be suppressed, thereby suppressing the deterioration of mechanical properties, and a flame-retardant polyester elastomer resin composition and flame-retardant polyester elastomer filament can be obtained that are excellent in flame retardancy, surface appearance and surface smoothness, toughness and resistance to deformation.

[0067] The thermoplastic resin used when preparing a masterbatch containing an organophosphorus compound may be the polyester elastomer described above, or other thermoplastic polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), or polybutylene naphthalate (PBN) may be used.

[0068] Furthermore, organophosphorus-containing compounds may be used together with polyester elastomers during the molding of the masterbatch.

[0069] In this embodiment, the composition ratio of the thermoplastic polyester elastomer and the organophosphorus-containing compound contained in the masterbatch is preferably such that 10 to 100 parts by mass of the organophosphorus-containing compound is melt-mixed with 100 parts by mass of the polyester elastomer, in order to suppress a decrease in the processability of the resulting polyester elastomer and to obtain excellent flame retardancy. More preferably, the amount is such that 20 to 70 parts by mass is melt-mixed with the organophosphorus-containing compound, in order to suppress aggregation of the organophosphorus-containing compound and improve the surface appearance and surface smoothness.

[0070] Examples of triazine skeleton-containing compounds include melamine cyanurate, melamine, cyanuric acid, isocyanuric acid, triazine derivatives, isocyanurate derivatives, etc., with melamine cyanurate being preferred.

[0071] Melamine cyanurate is preferably in granular (powder) form. Furthermore, melamine cyanurate may be untreated or surface-treated with a coupling agent (especially a silane coupling agent).

[0072] Other triazine skeleton-containing compounds that can be suitably used include compounds having a triazine ring in a hindered amine structure, which are generally used as radical scavengers. When a triazine ring-containing hindered amine compound is added to a polyester elastomer, it not only provides a general weather resistance improvement effect but also an improved flame retardancy effect.

[0073] This is because the combustion suppression effect can be obtained through a synergistic effect in which the triazine skeleton-containing hindered amine compound contributes as a radical scavenger to the chain reaction mediated by active radicals during the combustion process of polyester elastomers.

[0074] Due to the presence of a hindered amine structure, aggregation of triazine rings is suppressed in triazine skeleton-containing compounds, potentially improving their dispersibility. As a result, the resulting polyester elastomer exhibits improved surface appearance, surface smoothness, toughness, and resistance to deformation.

[0075] The hindered amine compound is preferably a triazine ring-containing N-alkoxyhindered amine compound. Compared to NH-type and NR-type hindered amine compounds, triazine ring-containing N-alkoxyhindered amine compounds generate nitrooxide radicals with high radical scavenging ability during combustion, and tend to exhibit better flame retardancy compared to alkyl-substituted hindered amine compounds.

[0076] Triazine ring-containing N-alkoxyhindered amine compounds include, specifically, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-1,3,5-triazine-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-1,3,5-triazine-6-yl]-1,12-dimethyl-1,5,8,12-tetraazadodecane, etc. A commercially available example is Flamestab NOR116FF manufactured by BASF Japan Ltd.

[0077] The content of the triazine skeleton-containing compound is preferably 1% by mass or more, and more preferably 3% by mass or more, relative to the entire core. Furthermore, the content of the triazine skeleton-containing compound is preferably 30% by mass or less, and more preferably 10% by mass or less, relative to the entire core. When the content of the triazine skeleton-containing compound is within the above range, the resulting polyester elastomer has excellent flame retardancy, as well as excellent toughness, resistance to deformation, and surface appearance.

[0078] Returning to the overall explanation of the first flame retardant, the total amount of the organic phosphate ester compound, phosphinate metal salt, and triazine skeleton-containing compound is preferably 1% by mass or more, and more preferably 10% by mass or more, relative to the core. Furthermore, the total amount of the organic phosphate ester compound, phosphinate metal salt, and triazine skeleton-containing compound is preferably 30% by mass or less, and more preferably 20% by mass or less, relative to the core. By having the total amount of the organic phosphate ester compound, phosphinate metal salt, and triazine skeleton-containing compound within the above range, the resulting fabric is less prone to scum formation during spinning and knitting processes, and exhibits greater stability and superior flame retardancy.

[0079] Returning to the explanation of the core as a whole, the core content should be 60% by volume or more, preferably 70% by volume or more, relative to the core-sheath composite fiber. Furthermore, the core content should be 90% by volume or less, and more preferably 80% by volume or less, relative to the core-sheath composite fiber. By having a core content of 60% by volume or more, the resulting fabric will not impair heat shrinkability and will exhibit superior seating comfort. On the other hand, by having a core content of 90% by volume or less, the resulting fabric will be less prone to scum formation during spinning and knitting processes, and will exhibit greater stability and superior flame retardancy.

[0080] (Sheath) The sheath portion contains polyester excluding the polyester elastomer contained in the core portion described above. The sheath portion also preferably contains a second flame retardant.

[0081] (Polyester excluding the polyester elastomer contained in the core) The polyester excluding the polyester elastomer in the core is not particularly limited. For example, the polyester excluding the polyester elastomer in the core is polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), etc. Among these, the polyester excluding the polyester elastomer in the core is preferably PET from the viewpoint of productivity.

[0082] (Second flame retardant) The sheath portion preferably contains a second flame retardant. The second flame retardant is not particularly limited. For example, the second flame retardant preferably contains at least one of an arylphosphinic acid compound or an alkylphosphinic acid compound. Furthermore, it is more preferable that at least one of the arylphosphinic acid compound or the alkylphosphinic acid compound is copolymerized with the polyester. By including at least one of the arylphosphinic acid compound or the alkylphosphinic acid compound as the second flame retardant, the resulting fabric is less prone to scum formation during spinning and knitting processes, and exhibits greater stability, superior appearance, and flame retardancy. When the second flame retardant is an arylphosphinic acid compound or an alkylphosphinic acid compound, it is even more preferable that they are added to the polymerization system before polycondensation after transesterification, or in the initial stages of the polycondensation reaction, and copolymerized into the polyester main chain.

[0083] The arylphosphinate compound is not particularly limited. For example, arylphosphinate compounds include 2-carboxyethyl(phenyl)phosphinate, 2-carboxyethyl(naphthyl)phosphinate, and 2-carboxyethyl(toluyl)phosphinate. Among these, 2-carboxyethyl(phenyl)phosphinate is preferred.

[0084] The alkylphosphinic acid compound is not particularly limited. For example, alkylphosphinic acid compounds include 2-carboxyethylmethylphosphinic acid and 2-carboxyethyl-tert-butylphosphinic acid. Among these, 2-carboxyethylmethylphosphinic acid is preferred as the alkylphosphinic acid compound.

[0085] The content of the second flame retardant is preferably 0.3% by mass or more, more preferably 0.5% by mass or more, and even more preferably 0.6% by mass or more, relative to the sheath, in terms of phosphorus element. Furthermore, the content of the second flame retardant is preferably 1.1% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.9% by mass or less, relative to the sheath, in terms of phosphorus element. By having the content of the second flame retardant within the above range, the resulting fabric is less prone to scum formation during spinning and knitting processes, and exhibits greater stability and superior flame retardancy.

[0086] Returning to the explanation of the sheath as a whole, the sheath content should be 10% by volume or more, preferably 20% by volume or more, relative to the core-sheath composite fiber. Furthermore, the sheath content should be 40% by volume or less, and more preferably 30% by volume or less, relative to the core-sheath composite fiber. When the sheath content is 10% by volume or more, the resulting fabric is less prone to scum formation during spinning and knitting processes, exhibiting greater stability and superior flame retardancy. On the other hand, when the sheath content is 40% by volume or less, the resulting fabric can be made less susceptible to loss of heat shrinkage.

[0087] Returning to the overall description of the fabric, the monofilament content in the fabric should be 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more. By having a monofilament content of 50% by mass or more, the resulting fabric will exhibit an appropriate amount of deflection when attached to a frame member.

[0088] The fineness of the monofilament is preferably 300 dtex or higher, and more preferably 500 dtex or higher. Furthermore, the fineness of the monofilament is preferably 3000 dtex or lower, and more preferably 2000 dtex or lower. A monofilament fineness of 300 dtex or higher results in superior strength of the fabric. On the other hand, a monofilament fineness of 3000 dtex or lower results in superior process passability. The fineness of the monofilament can be calculated based on JIS L 1018(2010) 8.7.1.

[0089] The dry heat shrinkage rate of the monofilament is preferably 5.0% or more, more preferably 10.0% or more, and even more preferably 20.0% or more. Furthermore, the dry heat shrinkage rate of the monofilament is preferably 50.0% or less, more preferably 45.0% or less, and even more preferably 40.0% or less. When the dry heat shrinkage rate of the monofilament is within the above range, the resulting fabric shrinks appropriately when heat is applied, making it easy to attach to the frame member. In addition, the fabric is easily adjusted to have an appropriate amount of deflection when attached to the frame member. The dry heat shrinkage rate of the fiber can be adjusted by the base polymer constituting the fiber, the core-sheath ratio, the type of flame retardant, the amount of flame retardant added, and the yarn production conditions. A monofilament that is a core-sheath composite fiber containing a polyester elastomer with a fineness of 300 to 3000 dtex and whose dry heat shrinkage rate is adjusted to 5.0 to 50.0% can be suitably used in the fabric of the present invention. Furthermore, the dry heat shrinkage rate can be measured based on JIS L 1013(8.18.2)(2010) Method B (filament shrinkage rate).

[0090] The melting point of the core-sheath composite fiber constituting the monofilament is not particularly limited. For example, the melting point of the core-sheath composite fiber is preferably 200°C or higher, and more preferably 225°C or higher. Furthermore, the melting point of the core-sheath composite fiber is preferably 280°C or lower, and more preferably 260°C or lower. When the melting point of the core-sheath composite fiber is within the above range, the resulting fabric has improved durability, such as abrasion resistance.

[0091] Furthermore, the melting point of the core is not particularly limited. For example, the melting point of the core is preferably 200°C or higher, and more preferably 210°C or higher. Also, the melting point of the core is preferably 230°C or lower, and more preferably 220°C or lower. On the other hand, the melting point of the sheath is not particularly limited. For example, the melting point of the sheath is preferably 225°C or higher, and more preferably 235°C or higher. Also, the melting point of the sheath is preferably 280°C or lower, and more preferably 260°C or lower. By having the melting points of the core and sheath within the above ranges, the resulting fabric will have improved durability, such as abrasion resistance.

[0092] The method for manufacturing monofilaments, which are core-sheath composite fibers, is not particularly limited. For example, monofilaments can be manufactured by a conventionally known core-sheath composite spinning method using co-extrusion equipment. According to the core-sheath composite spinning method, monofilaments can be produced with high productivity and at low cost.

[0093] More specifically, the first flame retardant and polyester elastomer constituting the core and the polyester constituting the sheath are melted in separate extruders, then each is measured using a gear pump and introduced into a composite pack. The two polymers constituting the core and sheath that have entered the composite pack are filtered through a metal nonwoven fabric filter or metal mesh within the pack, then introduced into a composite die, where the core is spun out in a form surrounded by the sheath.

[0094] Furthermore, when imparting functions such as dope dyeing, lightfastness, and antibacterial properties to a monofilament, a master tip containing a large amount of the desired pigment, lightfastener, and antibacterial agent can be prepared, and these can be mixed in the required amounts with the first flame retardant and polyester elastomer constituting the core, and / or the polyester constituting the sheath, before spinning.

[0095] The molten monofilament spun from the composite die can be efficiently produced as a core-sheath composite fiber by cooling, stretching, and heat-setting according to a standard procedure.

[0096] Furthermore, the fabric may contain fibers other than the monofilaments mentioned above. For example, the fibers other than monofilaments are synthetic fibers that are multifilaments. Among these, polyester multifilaments and polyamide multifilaments are preferred. The multifilaments may be processed yarns that have undergone processing such as false twisting. Among these, the fibers other than monofilaments are preferably false-twisted PET from the viewpoint of improving the texture and feel of the fabric and productivity. The content of these fibers other than monofilaments is less than 50% by mass, and preferably 40% by mass or less.

[0097] The fabric may be knitted or woven. In this embodiment, the fabric is preferably knitted because it offers superior elasticity, resulting in better seating comfort, improved breathability, and a wide variety of patterns.

[0098] The knitted fabric preferably has a knitting density of 10 threads / 25.4 mm or more in at least one of the warp direction and the weft direction, more preferably 15 threads / 25.4 mm or more. The knitting density is preferably 50 threads / 25.4 mm or less, more preferably 40 threads / 25.4 mm or less. When the knitting density is within the above range, the resulting fabric (knitted fabric) that has an appropriate deflection amount and strength when attached to a frame member can be easily obtained. As a result, the obtained fabric body exhibits more excellent seating comfort and air permeability.

[0099] The fabric preferably has a deflection amount of 20 mm or more when a load of 400 N is applied to the central portion, more preferably 30 mm or more. The deflection amount is preferably 60 mm or less, more preferably 50 mm or less. When the deflection amount is within the above range, the fabric body obtained using the fabric can have a deflection amount within a suitable range when a load is applied to the support surface that supports the user (for example, when the fabric body is the backrest or seat portion of a seating seat). As a result, the obtained fabric body has excellent seating comfort. In addition, the obtained fabric body can also maintain appropriate elasticity. The central portion of the fabric refers to the center of gravity of the planar shape of the fabric. That is, for example, when the fabric has a polygonal shape, the center of gravity of the polygon is the central portion of the fabric.

[0100] In addition, the air permeability of the fabric is preferably 5 cm 3 / cm 2 / sec or more, more preferably 20 cm 3 / cm 2 / sec or more. The air permeability of the fabric is preferably 300 cm 3 / cm 2 / sec or less, more preferably 180 cm 3 / cm 2 / sec or less. When the air permeability of the fabric is within the above range, the resulting fabric body reduces the stuffy feeling when used by a user and can sufficiently support the body. In the present embodiment, the air permeability can be measured based on JIS L 1096 (8.27.1) (2010) Method A (Frazier method).

[0101] In this embodiment, the fabric contains a first flame retardant in the core of the core-sheath composite fiber that constitutes the monofilament. The first flame retardant contained in such a core is less likely to cause scum formation during processes such as spinning and knitting. As a result, the resulting fabric exhibits not only an excellent appearance but also excellent flame retardancy. For example, the flammability of the fabric is preferably such that the burning rate is 0 mm / min in the FMVSS 302 (horizontal method). This indicates that it extinguishes itself before the A mark. In the FMVSS 302 (horizontal method), a burning rate of 0 mm / min indicates self-extinguishing properties, thus demonstrating excellent flame retardancy. The flammability of the fabric is more preferably such that the judgment grade in the 20 mm vertical burning test (UL94V test) is V-0. In the 20 mm vertical burning test (UL94V test), a judgment grade of V-0 indicates even better flame retardancy.

[0102] (Frame member) The frame members are not particularly limited. The frame members are members that have sufficient strength to withstand the tension of the fabric when the fabric is fixed in a state where tension is applied in at least one direction. Specifically, the frame members can be metals such as iron, aluminum, and titanium, carbon, wood, or plastic. Among these, the frame members are preferably made of metal or carbon in terms of high strength, and more preferably of carbon in terms of weight reduction.

[0103] Returning to the overall description of the fabric body, the method of attaching the fabric to the frame members to create the fabric body is not particularly limited. Figure 1 is a schematic diagram illustrating the method of attaching the frame members to the fabric. Figure 2 is a schematic diagram of the fabric body.

[0104] As shown in Figure 1, the fabric 1 is a bag-shaped knitted fabric processed into a three-dimensional shape so that a frame member 2 can be inserted inside. The knitted fabric can be knitted using a weft knitting machine. The weft knit structure is not particularly limited. For example, the weft knit structure may be a jersey knit, garter stitch knit, smooth knit knit, rib knit knit, etc. The fabric 1 has an opening 1a formed for inserting the frame member. As shown in Figure 1, for example, a frame member that has been disassembled into two parts (a first frame member 2a and a second frame member 2b) is inserted through the opening 1a and assembled inside the fabric 1 to form a roughly rectangular frame member 2. Then, for example, by heat treatment, as shown in Figure 2, the fabric 1 shrinks due to the heat and adheres tightly to the frame member 2. This can form a seamless, adhesive-free fabric body 3. Fabrics formed without stitching or bonding can be used in a variety of applications where the formation of a three-dimensional fabric surface is desirable, despite being stitchless and bondless.

[0105] The uses of the fabric material of this embodiment are not particularly limited. For example, the fabric material is suitable for various types of seats because it maintains excellent flame retardancy and exhibits excellent seating comfort and breathability. More specifically, the fabric material is suitable for seats and backrests in office chairs, car seats, and seats for railway vehicles. [Examples]

[0106] The present invention will be described in detail below based on the examples. The present invention is not limited to these examples. Furthermore, the performance in the examples was measured by the following method.

[0107] [Measurement method] (1) Volume ratio of the core and sheath of the core-sheath composite fiber Monofilaments were collected from the fabric, cut perpendicular to the fiber axis, and the resulting cross-sections were observed using a digital microscope (Keyence VHX-6000). The diameters of the core and sheath were measured using the length measuring tool on the digital microscope, and the volume ratio of the core and sheath were determined from the cross-sectional area of ​​the monofilament and the respective cross-sectional areas of the core and sheath using the area measuring tool on the digital microscope. The number of observed samples was set to 10, and the average value was used. Values ​​were rounded to one decimal place. (2) Amount of phosphorus Seven g of the sample was melted and formed into a plate, and its intensity was measured by X-ray fluorescence analysis (Rigaku Corporation X-ray fluorescence analyzer 3270). The phosphorus element content (mass %) was then determined using a calibration curve previously prepared with samples of known content. (3) Melting point of the core and sheath of the core-sheath composite fiber Using a PerkinElmer DSC-7 differential scanning calorimeter, 10 mg of monofilament samples taken from fabric were measured from 30°C to 280°C at a heating rate of 10°C / min. The temperatures at which the extreme values ​​of the resulting melting endothermic curves were obtained were defined as the melting points. (4) Fineness of monofilament In accordance with JIS L 1018(2010)8.7.1, 25 monofilaments were extracted from the fabric, their length (mm) and mass (mg) were measured, and the fineness (dtex) of the monofilaments was determined using the following formula. T = W / L × 100 Here, T: Fineness (dtex) W: Total mass of 25 filaments (mg) L: Total length of 25 filaments (mm) (5) Dry heat shrinkage rate of monofilament The measurement was performed according to JIS L 1013 (8.18.2) (2010) Method B (filament shrinkage rate). An initial load was applied to the sample, and two points were marked at a precise 500 mm interval. After removing the initial load, the sample was suspended in a dryer set to 185°C for 15 minutes before being removed. After cooling to room temperature, the initial load was applied again, and the length between the two points (mm) was measured. The dry heat shrinkage rate (%) was calculated using the following formula: ((500 - length between two points after heat treatment) / 500 × 100), and the average of five measurements was calculated. Here, the initial load was set according to the fineness of the sample, in accordance with JIS L 1013 (8.5.1). (6) Spinning properties Continuous spinning was performed for 12 hours, and four items (filter clogging, scum generation, yarn breakage, and number of knots) were evaluated according to the following criteria. The overall evaluation of the four items was given in two stages: "○" if all four items were "○", and "×" if even one of the four items was "×". A. Filter clogging ○: There was no filter clogging, the discharge state was stable, and there were no problems with spinning. ×: The filter became clogged, the discharge state became unstable, and the increase in filtration pressure made spinning impossible. B. Scum formation ○: No scum was generated during the silk reeling process. ×: Scum formation was confirmed in the silk reeling process. C. Thread breakage ○: Thread breakage occurred once or less. ×: Thread breakage occurred two or more times. D. Number of knots ○: The occurrence of knotted threads exceeding +20% of the average monofilament diameter was less than 10 times per ton. ×: More than 10 instances per ton of knotted filaments were generated, with a diameter exceeding +20% relative to the average monofilament diameter. The number of times knots were generated was expressed as: total weight of extruded polymer (kg) / 1000 kg × number of knots generated. (7) Air permeability Measurements were taken according to JIS L 1096(8.27.1)(2010) Method A (Fragile method). 20cm x 20cm test specimens were taken from five different locations on the fabric, and the specimens were attached to one end (intake side) of the cylinder using a Fragile type testing machine. When attaching the specimens, the specimens were placed on top of the cylinder, and a load of approximately 98N (10kgf) was applied evenly from above the specimens to prevent air leakage at the attachment point, without blocking the intake. After attaching the specimens, the intake fan was adjusted using a regulator so that the inclined barometer showed a pressure of 125Pa. The amount of air passing through the specimens was determined from the pressure shown by the vertical barometer at that time and the type of air vent used, according to the table attached to the testing machine, and the average value for the five specimens was calculated. (8) Deflection when a 400N load is applied For a fabric body having fabric stretched over a frame member, the amount of deflection under a 400N load was measured using a static load deflection tester for sheets (manufactured by Nidec-Shimpo Corporation, FGS-TV). Specifically, a fabric body was obtained by stretching fabric over a frame member made of metal. Next, the fabric body was placed on a fixed jig 30 cm high, and an initial load of 5N was applied using a horizontally elongated elliptical pressure plate measuring 250 mm x 300 mm, such that the load center of the pressure plate overlapped with the center of the fabric. The load center of the pressure plate at this time was taken as the origin. First, as a preliminary compression, a load up to 900N was applied at a speed of 50 mm / min, then the load was removed at a speed of 50 mm / min, and after being left for 1 minute, the load was similarly applied and removed up to a load of 900N at a speed of 50 mm / min, and the amount of deflection from the origin at each load application was measured. In this context, "amount of deflection when a 400N load is applied" refers to the amount of deflection from the origin when a 400N load is applied to the fabric. There are no particular restrictions on the orientation of the fabric when it is fixed to the frame fixing jig; it can be in either the vertical or horizontal direction. (9) Flammability (horizontal method) Three test pieces, each measuring 250 mm in length and 120 mm in width, were randomly selected from the fabric in both the vertical and horizontal directions. Next, they were evaluated based on FMVSS 302 (horizontal method). The test pieces were clamped in a special fixture, positioned horizontally, and a 38 mm flame was applied to one end for 15 seconds. The burning time (seconds) until the piece reached the 254 mm distance between mark A and mark B was measured. If the piece did not reach mark B, the burning distance (mm) and its burning time (seconds) were recorded. If the piece did not reach mark A, the burning distance was recorded as 0 mm and the burning time as 0 seconds. The burning rate was then calculated for both the vertical and horizontal directions of the fabric using the following formula 1, based on the measured burning time and burning distance. Here, "flammability (horizontal method)" refers to the average burning rate of the three test pieces in both the vertical and horizontal directions of the fabric. Equation 1: Combustion speed (mm / min) = Combustion distance (mm) / Combustion time (seconds) × 60 (10) Flammability (UL94V) Five test pieces, measuring 125 mm in length and 13 mm in width, were randomly selected from the fabric in both the vertical and horizontal directions. Next, they were evaluated based on the 20 mm vertical flammability test (UL94V test) according to the UL94 standard. Here, UL is a safety standard for electronic equipment established and authorized by Underwriters Laboratories Inc. in the United States, and UL94 is also a flame retardancy standard. After evaluation, the flammability (UL94V) grade was determined according to the established criteria. Flammability (flame retardancy) has three grades: V-0, V-1, and V-2, ranked in the order of V-0 > V-1 > V-2, with V-0 indicating the best flame retardancy among the three grades. In this test, all 10 pieces in total, both vertically and horizontally, met the V-0 criteria. V-2 was defined as a condition where at least one of the 10 tiles in the vertical and horizontal directions met the V-2 criteria. (11) Overall evaluation The overall evaluation of the obtained fabric samples was carried out according to the following criteria. ◎: The amount of deflection of the fabric when a 400N load is applied is in the range of 20 to 60 mm, the flammability of the fabric (horizontal method) is a burning rate of 0 mm / min and the flammability (UL94V) rating is V-0, and the overall evaluation of the spinnability of the monofilament used in the fabric is ○. ○: Fabrics whose deflection under a 400N load is in the range of 20-60mm, whose flammability (horizontal method) is a burning rate of 0mm / min, whose flammability (UL94V) grade does not meet V-0, or / and whose overall evaluation of the spinnability of the monofilament used in the fabric is ×. ×: Fabrics that satisfy at least one of the following conditions when a 400N load is applied: deflection of less than 20 mm or more than 60 mm, or flammability of the fabric (horizontal method) exceeds 0 mm / min.

[0108] [Reference example] (pellet) The constituent materials were dry-blended, melt-kneaded at a temperature of 240°C using a twin-screw extruder with a 45mm diameter screw, extruded in strand form, and then pelletized into 3mm diameter, 3mm long pellets using a pelletizer. First, the method for producing polyester elastomer is shown.

[0109] (Method for manufacturing polyester elastomer (A1)) A polyester block copolymer (A1-1) was prepared, comprising 80% by mass of a high-melting-point crystalline segment (H1) mainly composed of crystalline aromatic polyester and 20% by mass of a low-melting-point polymer segment (L1) mainly composed of aliphatic polyether. 58.0 parts of terephthalic acid, 36.7 parts of 1,4-butanediol, and 15.0 parts of poly(oxytetramethylene) glycol with a number average molecular weight of approximately 1000 were charged together with 0.04 parts of titanium tetrabutoxide and 0.02 parts of mono-n-butyl-monohydroxytin oxide in a reaction vessel equipped with a helical ribbon-type stirring blade. The mixture was heated at 220-245°C for 3 hours, and the esterification reaction was carried out while draining the reaction water from the system. 0.2 parts of tetra-n-butyl titanate were added to the reaction mixture, followed by 0.05 parts of "Irganox" 1098 (a hindered phenol antioxidant manufactured by Ciba-Geigy). The mixture was then heated to 255°C, and the pressure in the system was reduced to 27 Pa over 50 minutes. Polymerization was carried out under these conditions for 1 hour and 50 minutes. The resulting polymer was extruded into water in strand form and cut into pellets. The melting point was 217°C.

[0110] (Method for manufacturing polyester elastomer (A2)) A polyester block copolymer (A2-1) was prepared, comprising 80% by mass of a high-melting-point crystalline segment (H2) mainly composed of crystalline aromatic polyester and 20% by mass of a low-melting-point polymer segment (L2) mainly composed of aliphatic polyether, with the high-melting-point crystalline segment (H2) composed of two acid components and a diol component. The two acid components were 45.0 parts terephthalic acid, 20.0 parts isophthalic acid, 41.6 parts 1,4-butanediol, and 18.5 parts poly(oxytetramethylene) glycol with a number average molecular weight of approximately 1000, along with 0.04 parts titanium tetrabutoxide and 0.02 parts mono-n-butyl-monohydroxytin oxide. These were charged together in a reaction vessel equipped with a helical ribbon-type stirring blade and heated at 190-220°C for 3 hours, carrying out the esterification reaction while draining the reaction water from the system. 0.15 parts of tetra-n-butyl titanate were added to the reaction mixture, followed by the addition of 0.05 parts of "Irganox" 1098 (a hindered phenol antioxidant manufactured by Ciba-Geigy). The mixture was then heated to 245°C, and the pressure in the system was reduced to 27 Pa over 50 minutes. Polymerization was carried out under these conditions for 1 hour and 50 minutes. The resulting polymer was extruded into water in strand form and cut into pellets. The melting point was 164°C.

[0111] (Method for manufacturing polyester (A3)) A slurry of 1100 parts by weight of terephthalic acid and 480 parts by weight of ethylene glycol was supplied over 3 hours to an esterification reaction vessel maintained at 245°C containing 1950 parts by weight of bishydroxyethyl terephthalate. The esterification reaction was carried out while the water generated during the esterification reaction was removed from the reaction system by distillation. 1300 parts by weight of the resulting low polymer was transferred to a polycondensation reaction vessel. Next, a slurry of 65 parts by weight of 2-carboxyethyl(phenyl)phosphinic acid and 150 parts by weight of ethylene glycol, prepared in advance, was added to the transferred low polymer 40 minutes before the start of the polycondensation reaction. Then, 500 ppm of antimony trioxide was added, and the reaction system was gradually heated from 250°C to 290°C, while simultaneously distilling off the ethylene glycol and reducing the pressure of the reaction system to 50 Pa. The slurry of 2-carboxyethyl(phenyl)phosphinic acid and ethylene glycol was prepared 50 minutes before the start of slurry addition to the polycondensation reaction system. When the predetermined agitator torque was reached, nitrogen was introduced into the reaction system to return to atmospheric pressure and stop the polymerization reaction. The mixture was then discharged in strand form from the bottom of the polymerization vessel, cooled and solidified, and then cut to obtain pellets of a phosphorus-containing flame-retardant polyester composition. The obtained phosphorus-containing polyester had an intrinsic viscosity of 0.75, a melting point of 239°C, and a phosphorus content of 0.67 wt%.

[0112] (Method for manufacturing polyester elastomer (A4)) A polyester block copolymer (A1-2) was prepared, comprising 65% by mass of a high-melting-point crystalline segment (H1) mainly composed of crystalline aromatic polyester and 35% by mass of a low-melting-point polymer segment (L1) mainly composed of aliphatic polyether. 101 parts of terephthalic acid, 50.0 parts of 1,4-butanediol, and 71.0 parts of poly(oxytetramethylene) glycol with a number average molecular weight of approximately 1400 were charged together with 0.06 parts of titanium tetrabutoxide and 0.04 parts of mono-n-butyl-monohydroxytin oxide in a reaction vessel equipped with a helical ribbon-type stirring blade. The mixture was heated at 190-225°C for 3 hours, and the esterification reaction was carried out while draining the reaction water from the system. 0.4 parts of tetra-n-butyl titanate were added to the reaction mixture, followed by 0.1 parts of "Irganox" 1098 (a hindered phenol antioxidant manufactured by Ciba-Geigy). The mixture was then heated to 245°C, and the pressure in the system was reduced to 27 Pa over 50 minutes. Polymerization was carried out under these conditions for 2 hours and 50 minutes. The resulting polymer was extruded into water in strand form and cut into pellets. The melting point was 208°C.

[0113] (Method for manufacturing polyester elastomer (A5)) A polyester block copolymer (A1-3) was prepared, comprising 50% by mass of a high-melting-point crystalline segment (H1) mainly composed of crystalline aromatic polyester and 50% by mass of a low-melting-point polymer segment (L1) mainly composed of aliphatic polyether. 88 parts terephthalic acid, 33.0 parts 1,4-butanediol, and 101 parts poly(oxytetramethylene) glycol with a number average molecular weight of approximately 1400 were charged together with 0.06 parts titanium tetrabutoxide and 0.04 parts mono-n-butyl-monohydroxytin oxide in a reaction vessel equipped with a helical ribbon-type stirring blade. The mixture was heated at 190-225°C for 3 hours, and the esterification reaction was carried out while draining the reaction water from the system. 0.4 parts of tetra-n-butyl titanate were added to the reaction mixture, followed by 0.1 parts of "Irganox" 1098 (a hindered phenol antioxidant manufactured by Ciba-Geigy). The mixture was then heated to 245°C, and the pressure in the system was reduced to 27 Pa over 50 minutes. Polymerization was carried out under these conditions for 2 hours and 50 minutes. The resulting polymer was extruded into water in strand form and cut into pellets. The melting point was 182°C.

[0114] (Method of manufacturing polyester (A6)) 100 parts by weight of dimethyl terephthalate, 57.5 parts by weight of ethylene glycol, 0.03 parts by weight of magnesium acetate dihydrate, and 0.03 parts by weight of antimony trioxide were melted at 150°C under a nitrogen atmosphere. The molten mixture was heated to 230°C over 3 hours while stirring, and methanol was distilled off to complete the transesterification reaction. After the transesterification reaction, an ethylene glycol solution (pH 5.0) prepared by dissolving 0.005 parts by weight of phosphoric acid in 0.5 parts by weight of ethylene glycol was added. The intrinsic viscosity of the polyester composition at this point was less than 0.2. Subsequently, the polymerization reaction was carried out at a final temperature of 285°C, and the pressure of the reaction system was reduced to 13 Pa to obtain a polyester with an intrinsic viscosity of 0.65 and a melting point of 265°C.

[0115] (Method of manufacturing polyester (A7)) A slurry of 1100 parts by weight of terephthalic acid and 480 parts by weight of ethylene glycol was supplied over 3 hours to an esterification reaction vessel maintained at 245°C containing 1950 parts by weight of bishydroxyethyl terephthalate. The esterification reaction was carried out while the water generated during the esterification reaction was removed from the reaction system by distillation. 1300 parts by weight of the resulting low polymer was transferred to a polycondensation reaction vessel. Next, a slurry of 46 parts by weight of (2-carboxyethyl)methylphosphinic acid and 150 parts by weight of ethylene glycol, prepared in advance, was added to the transferred low polymer 40 minutes before the start of the polycondensation reaction. Then, 500 ppm of antimony trioxide was added, and the reaction system was gradually heated from 250°C to 290°C, while simultaneously distilling off the ethylene glycol and reducing the pressure of the reaction system to 50 Pa. The slurry of (2-carboxyethyl)methylphosphinic acid and ethylene glycol was prepared 50 minutes before the start of slurry addition to the polycondensation reaction system. When the predetermined agitator torque was reached, nitrogen was introduced into the reaction system to return to atmospheric pressure and stop the polymerization reaction. The mixture was then discharged in strand form from the bottom of the polymerization vessel, cooled and solidified, and then cut to obtain pellets of a phosphorus-containing flame-retardant polyester composition. The obtained phosphorus-containing polyester had an intrinsic viscosity of 0.72, a melting point of 245°C, and a phosphorus content of 0.50 wt%.

[0116] [Example 1] (pellet) A polyester elastomer (A1) and a flame retardant (B1) were kneaded together to obtain pellets (A1-B1) containing the flame retardant and polyester elastomer. (B1) used was Teijin Limited's organophosphorus-containing compound "Fireguard" FCX-210.

[0117] (Monofilament) A monofilament was obtained by spinning a polymer containing a flame retardant and polyester elastomer (A1-B1) as the core polymer and polyester (A3) as the sheath polymer, according to the core-to-sheath ratio shown in Table 1. Here, the monofilament was a core-sheath composite fiber, with a core fraction of 70 vol% and a sheath fraction of 30 vol%. The spinnability was good, with no filter clogging, no scum generation, no yarn breakage, and no knot formation. The overall evaluation of spinnability was good. The dry heat shrinkage rate of the obtained monofilament was 23.0%. The flame retardant contained in the sheath was phosphorus compound 1 (2-carboxyethyl(phenyl)phosphinic acid), and the phosphorus element content in the sheath was 0.7 mass%.

[0118] (fabric) The obtained monofilament and a double-ply false-twist polyester yarn of 167detx were used as other yarns, and a fabric was obtained by knitting on a weft knitting machine so that the monofilament content of the fabric was 70% by mass. Next, the edges of the fabric were supported and attached with a metal frame member with inner dimensions of 500 mm x 500 mm, and a fabric body was obtained in which shrinkage occurred by dry heat treatment (185°C x 15 minutes). The composition and performance of this fabric body are shown in Table 1. This fabric body had an overall evaluation of excellent spinnability, with the monofilament used in the fabric receiving a "○" rating, and excellent flammability, with a horizontal flammability of 0 mm / min. The amount of deflection of the fabric body when a 400 N load was applied was 32 mm, and the overall evaluation of the fabric body was excellent.

[0119] [Example 2] to [Example 10] Fabrics and fabric bodies were prepared and evaluated using the same method as in Example 1, except that the ratio of the core and sheath, the amount of flame retardant, and the amount of phosphorus were changed to match those listed in Table 1. The results are shown in Table 1.

[0120] [Example 11] Regarding the flame retardant contained in the core, fabrics and fabric bodies were prepared and evaluated using the same method as in Example 1, except that B2 was added to the flame retardant of Example 1. The results are shown in Table 1. (B2): Flamestab NOR116FF, a hindered amine light stabilizer (HALS) manufactured by BASF Japan Ltd.

[0121] [Example 12] Except for changing the flame retardant contained in the core from Example 1 to B3, the fabric and fabric body were prepared and evaluated using the same method as in Example 1. The results are shown in Table 1. (B3): Aluminum phosphinate OP-1240, manufactured by Clariant Chemicals. It does not have a melting point below 300°C, and its decomposition temperature is above 300°C.

[0122] [Example 13] Except for changing the flame retardant contained in the core from Example 1 to B4, the fabric and fabric body were prepared and evaluated using the same method as in Example 1. The results are shown in Table 1. (B4): Aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd., SB303, average particle size 27 μm)

[0123] [Example 14] The fabric and fabric body were prepared and evaluated using the same method as in Example 1, except that the flame retardant contained in the sheath portion was changed from Example 1 to B3. The results are shown in Table 1. (B3): Aluminum phosphinate OP-1240, manufactured by Clariant Chemicals. It does not have a melting point below 300°C, and its decomposition temperature is above 300°C.

[0124] [Example 15] The fabric and fabric body were prepared and evaluated using the same method as in Example 1, except that polyester elastomer (A1) and polyester elastomer (A2) were used in combination as the polymer for the core. The results are shown in Table 2.

[0125] [Example 16] The fabric and fabric body were prepared and evaluated using the same method as in Example 1, except that polyester (A6) that does not contain the element phosphorus as a flame retardant was used as the polymer for the sheath portion. The results are shown in Table 2.

[0126] [Example 17] The fabric and fabric body were prepared and evaluated in the same manner as in Example 1, except that a polyester (A7) copolymerized with phosphorus compound 2 was used as the polymer for the sheath portion. The results are shown in Table 2. Note that phosphorus compound 2 was (2-carboxyethyl)methylphosphinic acid, and the phosphorus element content in the sheath portion was 0.5% by mass.

[0127] [Example 18] Except for using polyester elastomer (A4) as the polymer for the core, the fabric and fabric body were prepared and evaluated using the same method as in Example 1. The results are shown in Table 2.

[0128] [Example 19] The fabric and fabric body were prepared and evaluated using the same method as in Example 1, except that polyester elastomer (A5) was used as the polymer for the core. The results are shown in Table 2.

[0129] [Comparative Example 1]~[Comparative Example 6] Fabrics and fabric bodies were prepared and evaluated using the same method as in Example 1, except that the ratio of the core and sheath, the amount of flame retardant, and the amount of phosphorus were changed to match those listed in Table 2. The results are shown in Table 3.

[0130] [Table 1]

[0131] [Table 2]

[0132] [Table 3] [Explanation of symbols]

[0133] 1 fabric 1a opening 2 Frame members 2a First frame member 2b Second frame member 3 Fabric body

Claims

1. Containing 50% or more by mass of monofilament, The aforementioned monofilament is a core-sheath composite fiber having a core portion and a sheath portion. The aforementioned core portion is Its melting point is 200-230°C. The aforementioned core-sheath composite fiber contains 60 to 90% by volume, and A first flame retardant and a polyester elastomer are included. The polyester elastomer contained in the core is a thermoplastic polyester elastomer. The first flame retardant described above is It comprises at least one selected from the group consisting of organic phosphate ester compounds, phosphinate metal salts, and triazine skeleton-containing compounds, The core portion contains 1 to 30% by mass, The aforementioned sheath contains a second flame retardant, The second flame retardant is It comprises at least one of an arylphosphinate compound or an alkylphosphinate compound, The aforementioned sheath contains 0.3 to 1.1% by mass in terms of phosphorus element, The aforementioned sheath portion is, Its melting point is 235-280°C. The aforementioned core-sheath composite fiber contains 10 to 40% by volume, and The core portion consists of polyester excluding the polyester elastomer, The polyester contained in the sheath portion is a fabric comprising at least one of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or polybutylene naphthalate.

2. The aforementioned fabric is a knitted fabric, The knitted fabric has a knitting density of 10 to 50 threads / 25.4 mm in at least one of the warp and weft directions. The fabric according to claim 1, wherein the fineness of the monofilament is 300 to 3000 dtex.

3. A fabric body comprising the fabric according to claim 1 or 2 and a frame member.

4. The fabric is formed without stitching or bonding, as described in claim 3.

5. A sheet using the fabric material according to claim 3 or 4.

Citation Information

Patent Citations

  • JP1972024171B

  • JP1973028006A

  • Nannenseihoriesuterusayashingatafukugoseni

    JP1976023325A

  • Conjugate fiber

    JP1991279429A

  • Elastic conjugate filament with highly flame-retardant property

    JP1999222729A